DEVELOPING ENGLISH LESSON PLANS FOR THE FIRST YEAR STUDENTS OF SMA 18 MAKASSAR BASED ON THE 2013 CURRICULUM - Djuwairiah Ahmad; Husnul Khatimah Nur (Langkawi: Journal of The Association for Arabic and English, 2016)
This research developed English lesson plans based on 2013 curriculum for the first year students of SMAN 18 Makassar. The research objectivewas to develop English lesson plans based on the 2013 curriculum. It was conducted at the first year students of SMAN 18 Makassar. The research product made the students more active in the teaching learning process. Then,the producthelped teachers to make or design good lesson plans based on the 2013 curriculum. The research design was Research & Development (R&D). It applied Borg & Gall model. The procedures were researching, collecting information, planning,preliminary form of product, main product revision, final product revision, dissemination, and implementation. The research data were qualitative and quantitative data. The research instruments were expert validation and teacher feedback sheet. The research findings showed that the product was valid to be implemented in the classroom. It can be seen from the scores given by the experts and teachers. The validation score of the product was 80%indicatingvery well. Then, the score from the teacher’s feedback was 95%. Therefore, the researcher concluded that English lesson plans based on 2013 curriculum developed by the researcher was very good with the score on 80%-95%.